2021
DOI: 10.1177/17543371211009485
|View full text |Cite
|
Sign up to set email alerts
|

Temporal kinematic and kinetics differences throughout different landing ways following volleyball spike shots

Abstract: Volleyball players often land on a single leg following a spike shot because of a shift in the center of gravity. This landing is one of the high-risk actions for non-contact ACL injury. The purpose of this study was to compare and analyze the discrete and temporal kinematics and kinetics associated with functional valgus collapse during volleyball in player landing phases during a single-leg landing and double-leg landing following a spike shot. Kinematics and kinetics data were collected (captured by a Vicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Therefore, onedimensional statistical parameter mapping (SPM) analysis is used to achieve the purpose of time series analysis of continuous data over a landing phase (Pataky et al, 2013). Previous studies have shown that ACL injury happens 30-50 milliseconds (about 15-25% landing phase) after initial ground contact (Krosshaug et al, 2007;Hogg et al, 2020;Xu et al, 2021b). The anterior tibia shear force acting on the proximal tibia is considered to be the primary source of ACL load, which is also the main shear force that causes ACL injury (Shelburne et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, onedimensional statistical parameter mapping (SPM) analysis is used to achieve the purpose of time series analysis of continuous data over a landing phase (Pataky et al, 2013). Previous studies have shown that ACL injury happens 30-50 milliseconds (about 15-25% landing phase) after initial ground contact (Krosshaug et al, 2007;Hogg et al, 2020;Xu et al, 2021b). The anterior tibia shear force acting on the proximal tibia is considered to be the primary source of ACL load, which is also the main shear force that causes ACL injury (Shelburne et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The negative value was defined as knee and hip adduction and ankle inversion. The integral of joint power over time and joint work was calculated, and negative (eccentric) work reflected the joint muscles' energy dissipation (Xu et al, 2021b). The individual joint work contribution to the total energy dissipation was calculated as the percentage of the joint energy dissipation in the total energy dissipation of the ankle, knee, and hip joints.…”
Section: Data Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared high-speed system with eight cameras (Vicon, Oxford Metric Ltd., Oxford, UK, 200 Hz) was set around the court for kinematics collection; force platform (AMTI, Watertown, MA, United States, 1,000 Hz) was set in the center of the court was used for kinetics data collection; they were synchronized in the movement test (Figure 1). A referred marker set with 20 reflex markers (diameter, 12.5 mm) (Xu et al, 2021b) was adopted in the current study. A standing trial was collected for the moralized calculation at the beginning of the test.…”
Section: Methodsmentioning
confidence: 99%
“…Discrete value analysis was widely used in studies whereas the single value analysis as neglects the time characteristics through the landing or take-off phase cannot represent the curve (Krosshaug et al, 2007;Xu et al, 2021b). At present, the research on the time-space variability of biomechanics has made great achievements, and statistical parametric mapping (SPM) has been proposed (Pataky, 2010;Pataky et al, 2013;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%